PENGARUH MANAJEMEN PENGETAHUAN, GAYA KEPEMIMPINAN DAN INSENTIF TERHADAP KINERJA PEGAWAI SERTA IMPLIKASINYA TERHADAP KINERJA ORGANISASI PADA KANTOR PELAYANAN PAJAK PRATAMA BANDA ACEH - Azhari Azhari; Said Musnadi; Mirza Tabrani (Jurnal Manajemen Inovasi, 2017)
Abstract The purpose of this study was to analyze: (1) the impact of knowledge management on employee performance (2) the effect of leadership style on employee performance, (3) the effect of incentives on employee performance (4) the effect of knowledge management on organizational performance (5) the effect of leadership style on the performance of the organization, (6) the effect of incentives on organizational performance, (7) the impact of employee performance to organizational performance (8) the effect of the influence of knowledge management on organizational performance through employee performance, (9) the effect of leadership style on organizational performance through employee performance (10) the effect of incentives on organizational performance through employee performance. This research was conducted at the Tax Office Primary Banda Aceh. As for the object of this research is knowledge management, knowledge management, incentives, employee performance, and organizational performance. The results show that knowledge management, leadership style, and incentives effect on employee performance, and knowledge management, leadership styles and incentives also have an influence on organizational performance. The results also proved that the performance of employees also affects the performance of the organization. The results based on the indirect effect is obtained explanation that knowledge management, leadership styles and incentives affect the performance of the organization through employee performance. The results of this study prove that either simultaneously or partial, knowledge management, leadership style and incentive effect on employee performance and organizational performance. Keywords        Knowledge Management, Leadership Style, Incentives, Employee Performance and Organizational Performance